NUMERICAL STUDY CONCERNING THERMAL RESPONSES OF NANOFILMS UNDER THE THERMOMASS THEORY - Freitas, R. S. M.; Stampa, C. S.; Lobão, D. C.; Alvarez, G. B. (Revista de Engenharia Térmica, 2016)
he Thermomass theory is based on the relationship mass-energy of Einstein, i.e., the heat has mass-energy duality, behaving as energy in processes where its conversion occurs in another form of energy, and behaving as mass in heat transfer processes. The mathematical model stablished by the Thermomass model falls within the class of problems called models non-Fourier heat conduction. The present work aims to analyze the thermal responses provided by Thermomass theory of nanofilms submitted to a very fast heating process using two different heat sources (laser pulses). During the process of analysis, the equations are written in conservation law, put into dimensionless form and discretized in the way that a high-order TVD scheme is used on to provide accurate and reliable numerical simulations for obtaining the thermal responses predicted by the Thermomass model. The results show that the Thermomass theory predicted a heterogeneous temperature distribution with elevated temperature peaks. The thermal responses obtained from this model may prevent the thermal damage caused by technologies of the processing and manufacturing of elements based on high-power laser applications.